Mr young has 30 times as many pencils as jack. The whole class has 200 times as many pencils as jack. If jack has 2pencils, how many pencils does mr young have ? And the whole school have?

Answers

Answer 1
Answer: well you would do 30*2= 60
and that would be your answer

Related Questions

Who is SohCahToa Joe? on Csi geometry:trigonometry I need the answers.
Which equation represents the line shown on the ​
Of the 125 guests invited to a wedding, 104 attented the wedding. What percent of invited guests attented the wedding?
Greg and Josh want to go whitewater rafting in 3 weeks. Josh is able to save the $480 he needs to go on the trip by saving the pay he received for 5 hours of work each week. Greg must save 8 hours worth of pay each week in order to have enough money. How much more money does Josh make than Greg? a. $10 b. $12 c. $14 d. $20
A snail travels at a rate of 2.35 feet per minute. Write a rule to describe the function. How far will the snail travel in 5 minutes?a. d(t) = 5t; 11.75 ft b. d(t) = t + 2.35; 7.35 ft c. d(t) = ; 2.13 ft d. d(t) = 2.35t; 11.75 ft

P + 4 Solve for p
--------- = 5
6

Answers

Answer:

p = 26

Step-by-step explanation:

(p+4)/6 = 5

Multiply each side by 6

(p+4)/6 *6 = 5*6

p+4 = 30

Subtract 4 from each side

p+4-4 = 30-4

p = 26

What is the product of 2x + y and 5x – y + 3?

Answers

Answer:  The required product is 10x^2-y^2+3xy+6x+3y.

Step-by-step explanation:  We are to find the product f the following two algebraic expressions:

E_1=2x+y,\n\nE_2=5x-y+3.

To find the product of the above two expressions, we must multiply each term of the first expression with each term of the second expression.

The multiplication is as follows:

M\n\n=E_1 * E_2\n\n=(2x+y)*(5x-y+3)\n\n=10x^2-2xy+6x+5xy-y^2+3y\n\n=10x^2-y^2+3xy+6x+3y.

Thus, the required product is 10x^2-y^2+3xy+6x+3y.

Answer: 10x^2-y^2+3xy+6x+3y

Step-by-step explanation:

Given expressions are 2x+ y and 5x -y +3

Product of 2x+y and 5x-y+3 is

(2x+y)* (5x-y+3) = 2x* (5x-y+3) + y* (5x-y+3) ( by applying distributive property under multiplication over addition)

(2x+y)* (5x-y+3) = 10x^2-2xy+6x+5xy-y^2+3y (again by distributive property)

(2x+y)* (5x-y+3) = 10x^2-y^2+3xy+6x+3y  ( by operating the like terms.)

If f(x)= -1x2+3, find f(1)
Someone help me, I'm so confused ;-;

Answers

Answer:

-1×(1)×2+3=1 This is the answer I think

10. 3x – x +4 = 4(2x-1) 11. 4(2x +1) = 5x + 3x +9

12. 10+ x = 5 (1/5x + 2)

13. 8 (x + 2) = 2x + 16

14. 3+ 3/2x + 4 = 4x – 5/2x

15. 3/2 (2x +6) = 3x +9

16. ½ (2-4x) +2x = 13

17. 12 + 2x – x = 9x +6

18. 4x +1 = 2 (2x + 3)

19. 4 (x + 3) - 4 = 8(½x + 1)

20. X + 5x + 4 = 3(2x – 1)

21. 5 (x + 2) - 3x = 2 (x +5)
solve all equations and show your work

Answers

Answer:

10.  x=4/3 or 1.3

11. No solution

12. All real numbers

13. x=0

14. No solution

15. All real numbers

16. No solution

17. x=3/4 or 0.75

18. No solution

Step-by-step explanation:

5/12+2/9+1/6 adding fractions

Answers

5/12 = 15/36
2/9 = 8/36
1/6 = 6/36
15 + 8 + 6 = 29/36
Happy to Help!
Find the lcd which is 36
15/36+8/36+6/36
=29/36

Which long division problem can be used to prove the formula for factoring the difference of two perfect cubes?

Answers

Some of the possible options of the questions are;

A) (a - b) | \overline  {a^2 + a \cdot b + b^2}

B) (a + b) | \overline  {a^2 - a \cdot b + b^2}

C) (a + b) | \overline  {a^3 + 0 \cdot a \cdot b^2 + 0 \cdot a \cdot b^2  - b^3}

D) (a - b) | \overline  {a^3 + 0 \cdot a \cdot b^2 + 0 \cdot a \cdot b^2  - b^3}

The difference of two perfect cubes has a binomial factor and a trinomial factor

The option that gives the long division problem that can be used to prove the difference of two perfect cubes is option D

D) \underline {(a - b) | \overline  {a^3 + 0 \cdot a \cdot b^2 + 0 \cdot a \cdot b^2  - b^3}}

Reason:

The formula for factoring the difference of twoperfect cubes is presented as follows;

a³ - b³ = (a - b)·(a² + a·b + b²)

Given that a factor of the difference of two cubes is (a - b), and that we

have; (a³ + 0·a·b² + 0·a²·b - b³) = (a³ - b³), both of which are present in

option D, by long division of option D, we have;

{} \hspace {33} a^2 +  a \cdot b + b^2\n(a - b) | \overline  {a^3 + 0 \cdot a \cdot b^2 + 0 \cdot a^2 \cdot b  - b^3}\n{} \hspace {33} \underline{a^3 - a^2 \cdot b }\n{} \hspace {55} a^2 \cdot b + 0 \cdot a \cdot b^2 + 0 \cdot a \cdot b^2  - b^3\n {} \hspace {55} \underline{a^2 \cdot b - a \cdot b^2}\n{} \hspace {89} a \cdot b^2  + 0 \cdot a \cdot b^2  - b^3\n{} \hspace {89} \underline{a \cdot b^2 - b^3}\n{}\hspace {89} 0

By the above long division, we have;

(a - b) | \overline  {a^3 + 0 \cdot a \cdot b^2 + 0 \cdot a \cdot b^2  - b^3} = a² + a·b + b²

Which gives;

(a - b) | \overline  {a^3 + 0 \cdot a \cdot b^2 + 0 \cdot a \cdot b^2  - b^3} = (a³ + 0·a·b² + 0·a·b² - b³)/(a - b)

We get;

(a³ + 0·a·b² + 0·a·b² - b³)/(a - b) = a² + a·b + b²

(a - b)·(a² + a·b + b²) = (a³ + 0·a·b² + 0·a·b² - b³) = (a³ - b³)

(a - b)·(a² + a·b + b²) = (a³ - b³)

(a³ - b³) = (a - b)·(a² + a·b + b²)

Therefore;

The long division problem that can be used to prove the formula for

factoring the difference of two perfect cubes is

(a - b) | \overline  {a^3 + 0 \cdot a \cdot b^2 + 0 \cdot a \cdot b^2  - b^3}, which is option D

D) (a - b) | \overline  {a^3 + 0 \cdot a \cdot b^2 + 0 \cdot a \cdot b^2  - b^3}

Learn more here:

brainly.com/question/17022755

Answer:

The correct options, rearranged, are:

Options:

A)(a^2+ab+b^2)/(a-b)\n\nB)(a^2-ab+b^2)/(a+b)\n\nC)(a^3+0a^2+0ab^2-b^3)/(a+b))\n\n D)(a^3+0a^2+0ab^2-b^3)/(a-b)

And the asnwer is the last option (D).

Explanation:

You need to find which long division can be used to prove the formula for factoring the difference of two perfect cubes.

The difference of two perfect cubes may be represented by:

  • a^3-b^3

And it is, as a very well known special case:

  • a^3-b^3=(a-b)(a^2+ab+b^2)

Then, to prove, it you must divide the left side,    a^3-b^3     , by the first factor of the right side,    a-b

Note that, to preserve the places of each term, you can write:

  • (a^3-b^3)=(a^3+0a^2+0ab^2-b^3)

Then, you have:

  • (a^3+0a^2+0ab^2-b^3)=(a-b)(a^2+ab+b^2)

By the division property of equality, you can divide both sides by the same factor, which in this case will be the binomial, and you get:

  • (a^3+0a^2+0ab^2-b^3)/(a-b)=(a^2+ab+b^2)

That is the last option (D).